The Permanence in a Single Species Nonautonomous System with Delays and Feedback Control - Xiaomei Feng; Fengqin Zhang (Discrete Dynamics in Nature and Society)
We consider a single species nonautonomous system with delays and feedback control. A general criterion on the permanence for all positive solutions is established. The results show that the feedback control does not influence the permanence of species.